Open for Learning: Encouraging Generalization Fosters Knowledge Transfer in Negotiation. (7th July 2019) - Kim, Jihyeon; Thompson, Leigh; Loewenstein, Jeffrey
Abstract: We examined whether encouraging managers to attend to underlying principles in negotiation training examples rather than contextual specifics fosters openness to learning and enhances subsequent knowledge transfer to new negotiation situations. In an experimental study, 420 managers read a negotiation case study example set in a familiar or unfamiliar industry and answered either broadening or narrowing questions about an example. Managers given broadening questions about an example set in an unfamiliar industry were more open to learning than managers who were asked narrowing questions about an example set in a familiar industry. Openness to learning in turn fostered successfully applying the key negotiation principle to resolve a subsequent face‐to‐face negotiation. The findings suggest that negotiation training for professionals is unlikely to meet its intended purpose if it relies on offering managers examples set in their own industries and encouraging them to answer questions about the contextual specifics of those examples.